I'm trying to show $\displaystyle \neg(a \vee b) \wedge [(\neg a) \wedge b] \leftrightarrow \neg a$

So far I've distributed and got $\displaystyle [\neg(a \vee b)\vee(\neg a)]\wedge[\neg(a \vee b) \vee b]$

Printable View

- Sep 22nd 2011, 10:00 PMJskidshowing to statments are equivalent
I'm trying to show $\displaystyle \neg(a \vee b) \wedge [(\neg a) \wedge b] \leftrightarrow \neg a$

So far I've distributed and got $\displaystyle [\neg(a \vee b)\vee(\neg a)]\wedge[\neg(a \vee b) \vee b]$ - Sep 23rd 2011, 02:42 AMPlatoRe: showing to statments are equivalent